IDENTIFIKASI KAPANG PADA TEMPE BUNGKUS DAUN PISANG DAN PLASTIK ASAL PENGRAJIN TEMPE JATIASIH, BEKASI - Qurrota Aýun; Sulis Suryani; Chery Kurnia (Bioed : Jurnal Pendidikan Biologi, 2022)
Tempe is prepared from soybean seed base through fermentation with yeast containing Rhizopus sp. The types of microorganisms in the growth of tempeh microflora are very diverse and have a role during fermentation and are very interesting to look at. The use of tempeh packaging produces compounds that cause tempeh to have a distinctive taste and aroma. The use of different wrappers in tempeh, it is likely that it can also affect the type of microorganisms that play a role at the time of fermentation.  This study aims to isolate the mold from tempeh craftsmen in Jatiasih, Pondok Gede.  The sample used was fresh tempeh wrapped in banana leaves and plastic from Jatiasih tempeh craftsman, Pondok Gede.The method used is direct plating on PDA media. Macroscopic observations were carried out by observing the color of conidia and mycelium, while microscopic observations were carried out with slide culture techniques, namely observing the shape of spora, columela, sporangiospora and hyphae.  The data are presented in the form of tables and figures and analyzed descriptively qualitatively. The results showed that in all samples of tempeh Jatiasih craftsmen predominantly contained molds suspected to be Rizhopus stolonifer  Keywords: Isolation, Rizhopus stolonifer; Tempeh, Wrap